Phytochemical screening analysis of Guava leaf extract (Psidium guajava L.) against the content of Saponins, Tannins, and Flavonoids - Faradilla, Meriza; Rizal, Khairul (Journal of Natural Sciences and Mathematics Research, 2023)
Guava is a plant with many benefits, especially in the leaves. There are many chemical compounds in guava leaves (Psidium guajava L.), such as flavonoids, tannins, and saponins. Traditionally, Guava leaves have been used for a long time (Psidium guajava L.) as medicine to stop diarrhea, with its availability as an herbal product widely marketed. Using guava leaves as traditional medicine is made by boiling them and extracting them to remove chemical compounds, namely, Tannins found in the leaves. In addition to decoction, guava leaf extract can be obtained by maceration. Research that has been conducted aims to determine the content of saponin compounds, tannins and flavonoids in guava leaves (Psidium guajava L.) using two extraction methods, namely maceration and boiling. The maceration method uses a technical ethanol solvent (96%), and boiling uses a water solvent. Then phytochemical screening is tested based on the color reagent of the compound. Based on the results of research that has been carried out shows that from both extraction methods, positive guava leaf extract (Psidium guajava L.) contains saponin compounds, tannins, and flavonoids.